2012
DOI: 10.12693/aphyspola.121.247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal Annealing and Film Thickness on the Structural and Morphological Properties of Titanium Dioxide Films

Abstract: Titanium dioxide (TiO 2 ) thin films having different thicknesses of 220, 260, and 300 nm were deposited onto well-cleaned n-type silicon substrates by reactive DC magnetron sputtering and annealed in the range of 200-1000 • C in steps of 200 • C. The effects of thermal annealing and thickness variation on the crystalline quality and surface morphology of the films were investigated by X-ray diffraction and atomic force microscopy measurements. It was found that the film quality and morphology depend on the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
(13 reference statements)
2
5
0
Order By: Relevance
“…It can be seen that the band gap energy decreased with the increasing grain sizes and thickness of TiO 2 thin films due to the increases annealing temperatures as summarized in Table 2. This suggests that the grain sizes increased linearly with thickness (Tayade et al 2007;Çörekçí et al 2011).…”
Section: Optical Absorption and Band Gapmentioning
confidence: 91%
“…It can be seen that the band gap energy decreased with the increasing grain sizes and thickness of TiO 2 thin films due to the increases annealing temperatures as summarized in Table 2. This suggests that the grain sizes increased linearly with thickness (Tayade et al 2007;Çörekçí et al 2011).…”
Section: Optical Absorption and Band Gapmentioning
confidence: 91%
“…The XRD results show that the TiO2G and TiO2P have the same fraction of anatase after heating, so the total amount of anatase in TiO2G is larger compared to TiO2P (vide supra). Ç örekçi et al noted a similar finding in their study of different thicknesses of TiO2 films heated at different temperatures [19]. The authors reported that the surface roughness of the thicker TiO2 film (300 nm) increased more compared to thinner films (220 and 260 nm) upon heating.…”
Section: Morphology Of the Tio2p And Tio2g Layer Before And After Hea...mentioning
confidence: 53%
“…It was observed that an increase in surface roughness and grain sizes occurred during heating depending on TiO 2 film thicknesses, which also increased with film thickness. This is because increasing temperatures transform TiO 2 from amorphous to anatase and then to rutile [17], and these phase transitions affect the surface morphology of the TiO 2 film, which includes the roughness and crystallinity of the surface [19].…”
Section: Introductionmentioning
confidence: 99%
“…The annealing can be performed in‐situ or ex‐situ , that is, inside the vacuum chamber immediately after the deposition or afterwards in a separate furnace, respectively. The post‐annealing temperature can influence the stress in the film structure, roughness, grain size, crystallinity and stoichiometry [45,47] . A high oxygen partial pressure and temperature around 500 °C promotes the diffusion of oxygen into the film and a reduction in the number of oxygen vacancies created during the film growth [48] .…”
Section: Impact Of Physical Parameters On the Film Growthmentioning
confidence: 99%